2022
DOI: 10.48550/arxiv.2201.01630
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chaos in Celestial CFT

Sabrina Pasterski,
Herman Verlinde

Abstract: Celestial holography proposes a duality between gravitational scattering in asymptotically flat spacetime and a conformal field theory living on the celestial sphere. Its dictionary relates the infinite dimensional space-time symmetry group to Ward identities of the CFT. The spontaneous breaking of these asymptotic symmetries governs the dynamics of the soft sector in the CFT. Here we show that this sector encodes non-trivial backreaction effects that exhibit characteristics of maximal quantum chaos. A key ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 56 publications
2
12
0
Order By: Relevance
“…In combination, these results hint at a structure that ties together the observation of our recent paper [16] on how signals of maximal quantum chaos are encoded in the superrotation Goldstone modes with the presence of celestial w 1+∞ symmetry [18]. Fortuitously, while the perspective in [16] ignored the w 1+∞ structure, it naturally led us to revisit 2D SYK models of the type proposed in [25]. These models precisely have these extra symmetries but hitherto lacked an obvious application or purpose for them.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations

Mapping SYK to the Sky

Pasterski,
Verlinde
2022
Preprint
Self Cite
“…In combination, these results hint at a structure that ties together the observation of our recent paper [16] on how signals of maximal quantum chaos are encoded in the superrotation Goldstone modes with the presence of celestial w 1+∞ symmetry [18]. Fortuitously, while the perspective in [16] ignored the w 1+∞ structure, it naturally led us to revisit 2D SYK models of the type proposed in [25]. These models precisely have these extra symmetries but hitherto lacked an obvious application or purpose for them.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, for the version of the model considered in [25], it was found that the IR Schwinger-Dyson equation exhibits conformal symmetry and that the emergent pseudo-Goldstone action arising from broken reparameterization invariance matches the boundary action derived from 3D AdS gravity. This latter match hints at a potential application to celestial holography, given the analysis in our recent paper [16].…”
Section: A 2d Generalization Of Syksupporting
confidence: 68%
See 2 more Smart Citations

Mapping SYK to the Sky

Pasterski,
Verlinde
2022
Preprint
Self Cite
“…In [8], the supersymmetric w 1+∞ algebra has been identified with the corresponding soft current algebra in the supersymmetric Einstein-Yang-Mills theory. The relevant works on the celestial holography in the various directions can be found in [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35]. See [1] for more complete literatures.…”
Section: Introductionmentioning
confidence: 99%